Nasal Obstruction: Overview of Pathophysiology and Presentation of a Clinically Relevant Preoperative Plan for Rhino(Septo)plasty - Snoeks, Simon; Velasco, Enrique; Talavera, Karel; Hellings, Peter W. (Facial Plastic Surgery, 2024)
Impairment of nasal breathing is a highly prevalent and bothersome symptom that affects daily functioning and/or sleep quality. Those surgeons dealing with patients seeking rhinoplasty need to carefully analyze the preoperative nasal breathing capacity and predict the positive or even negative impact of rhino(septo)plasty on nasal breathing. Given the lack of correlation between the subjective feeling of suboptimal nasal breathing and the objective measurements of nasal flow and nasal resistance, a critical and mainly clinical evaluation of all anatomical, mucosal, and sensory mechanisms involved in nasal obstruction is mandatory. Indeed, thermo-, mechano-, and chemosensory receptors on the nasal mucosa, airflow, and respiratory dynamics might all contribute to the overall perception of nasal breathing capacity. In this review, we provide an overview of the factors determining suboptimal nasal breathing including different diagnostic and experimental tests that can be performed to evaluate nasal flow and nasal resistance and current limitations in our understanding of the problem of nasal breathing in an individual patient. An algorithm for the preoperative or diagnostic workup for nasal obstruction is included that might be useful as a guide for clinicians dealing with patients seeking nose surgery.
Keywords: nasal obstruction; preoperative evaluation; rhinoplasty